Implementasi Pembelian Emas Pada Produk Simpanan Emas Di Gerai Dinar Pekalongan Menurut Fatwa DSN – MUI - Fadli Hudaya; Y Yohani; Wahyu Intan Pertiwi (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2022)
Saving is highly recommended for Muslims to prepare for the future when something unexpected happens. One of the agencies that offer Gold Savings products is the Pekalongan Dinar Outlet. It founded by several people who focus on economic development, especially in the field of purchasing gold with sharia principles. As we know, gold is an item that is traded and is very flexible in nature for investment. The purpose of this study was to determine the mechanism of buying gold, purchasing suitability, and storing gold against the DSN-MUI Fatwa on Gold Savings products at Pekalongan Dinar outlets. Since it is field research, with qualitative method, the procedures of collecting data are observations, interviews, and documentations. The analysis method conducted by collecting data related to Gold Savings products at Pekalongan Dinar outlets. The sale and purchase of gold at the Pekalongan Dinar outlet is in accordance with the DSN-MUI fatwa no 77/DSN-MUI/V/2010 concerning non-cash buying and selling of gold. The concept of sharia in the Gold Savings product at the Pekalongan Dinar Outlet is in accordance with the DSN-MUI fatwa No. 02/DSN-MUI/IV/2000 concerning Savings. Likewise with the pillars and conditions in carrying out a wadiah contract, it also fulfils Islamic law. Keywords: DSN-MUI Fatwa, Gold Purchasing, Gold Purchasing